PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PT. EKA MAJU SEJAHTERA - Nino Nopriandi; Alda Widyawati Yusuf (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose to analyze the effect of service quality and company image on customer satisfaction of PT. Eka Maju Sejahtera. This research is included in the category of causal associative research using a quantitative approach. The population in this study were customers of PT. Eka Maju Sejahtera. The sampling technique for this research uses simple random sampling. This research used a sample size using the Slovin formula. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially, service quality and company image have a positive and significant effect on customer satisfaction at PT. Eka Maju Sejahtera.